Survival Analysis Of Diabetes Mellitus At RSUP Dr. Tadjuddin Chalid Makassar (Jurnal Matematika, Statistika dan Komputasi, 2026)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia and disturbances in the metabolism of carbohydrates, fats, and proteins, resulting from an absolute or relative deficiency in insulin secretion or action. The prevalence of DM in Indonesia continues to rise, reaching 2.2% in 2023. In South Sulawesi, Makassar City exhibits a particular urgency with a prevalence of 2.14%, a figure significantly exceeding the provincial average. This study aims to determine the survival probability of inpatients with diabetes mellitus at RSUP Dr. Tadjuddin Chalid Makassar using the Kaplan-Meier method. Based on the analysis, the results indicate that the survival probability of hospitalized diabetes mellitus patients is 0.649 or 64.9%.Keywords:  Survival Analysis, Kaplan-Meier, Diabetes Mellitus
Keywords: analisis survival; Kaplan-Meier; Diabetes Mellitus